Brief commentary on the impact of global climate change on fisheries and aquaculture with special reference to India - Dutta, Joystu; Sen, Tirthankar; Mitra, Ankita; Zaman, Sufia; Mitra, Abhijit (Bangladesh Journal of Zoology, 2021)
Abstract not available Bangladesh J. Zool. 48(2): 457-463, 2020